FORMATION OF CORPORATE INFORMATION SYSTEMS (CIS) IN THE OIL AND GAS COMPLEX OF RUSSIA - Alexander Gladilin; Natalya Rudenko (Вестник Северо-Кавказского федерального университета, 2022)
The article discusses the formation of corporate information systems in the oil and gas sector in the Russian Federation. A general scheme of the algorithm for theirimplementation at enterprises is proposed, methods and forms of their implementation are determined. The classification and main characteristics of the recommended CIS are given.